Konsep Tasawuf Menurut Imam Al-Ghazali - Fasya, Adib ‘Aunillah (Journal of Sufism and Psychotherapy, 2022)
This study aims to describe the concept of Sufism which was formulated by Imam al-Ghazali. In the Islamic world, Imam al-Ghazali is known as one of the most influential figures in the development of the world of Sufism. The method used in this research is qualitative with the type of library research (library research). Data sources were taken from books, journals, articles and other related references. The results of this study are the concept of Sufism from Imam Al-Ghazali which means sincerity to God and good association with fellow human beings. Sufism contains two elements. First, human relationship with God and human relationship. Second, the relationship is based on morality. Relationship with God is based on sincerity (sincerity of intention), which is marked by eliminating self-interest from fulfilling God's commands. Then, when human relations are based on social ethics, one thing that is done is to place the interests of others above personal interests as long as these interests do not conflict with Sharia law. Because according to Imam Al-Ghazali, anyone who deviates from the Shari'a is not a Sufi. If he claims to be a Sufi, his claim is a lie. Imam al-Ghazali touched on three problems of Sufism, namely reclaiming the discipline of Sufism from spiritual elements that are far unrelated to Islamic teachings so that Sufism is ultimately in accordance with Islamic law, synthesizing moderation and balance between the values of fiqh (shariah) and tasawuf which previously contradictory, and continues the previous contribution of succeeding in establishing Sufism as a spiritual aspect of Islamic doctrine, where it is widely accepted by the Muslim community. Al-Ghazal's concept and influence is widespread in Sunni Muslim communities in the Middle East and in various countries including Indonesia.